Sharia Digital Marketing Strategy through Shopee and TikTok Shop in Increasing Sales of Hijab Products - Luthfi Hadi Aminuddin; Siswanto (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2026)
This study aims to analyze the Islamic digital marketing strategy implemented by Giyanda.co through Shopee and TikTok Shop to increase sales of hijab products, identify the reasons for using both platforms, and examine their impact on business development. This research employed a qualitative case study design. Data were collected through observation, in-depth interviews, and documentation. The informants were the business owner and the employees involved in Giyanda.Co’s digital marketing activities. Data were analyzed through data reduction, data display, and conclusion drawing. The findings reveal that Giyanda.co implements its Islamic digital marketing strategy by optimizing various features of Shopee and TikTok Shop, including live streaming, short-video content, hashtags, vouchers, discounts, and flash sales. In practice, the company emphasizes Islamic marketing principles, such as honesty, transparency in product information, fair pricing, and ethical communication, in line with Islamic values. The primary reason for choosing Shopee and TikTok Shop is their complementary functions: Shopee serves as a secure, trusted transaction platform, while TikTok Shop serves as a promotional medium that can reach a broader audience through interactive, potentially viral content. The implementation of these strategies has resulted in increased sales volume, wider market reach, enhanced brand awareness, stronger customer trust, and greater customer loyalty, as reflected in repeat purchases and positive customer reviews. This study concludes that integrating digital marketing with Islamic marketing principles is an effective strategy for increasing sales while fostering long-term relationships between businesses and consumers. The findings contribute to the development of Islamic digital marketing literature, particularly for Muslim fashion businesses operating on social commerce platforms